2016
DOI: 10.1111/nph.13830
|View full text |Cite
|
Sign up to set email alerts
|

Online CO2 and H2O oxygen isotope fractionation allows estimation of mesophyll conductance in C4 plants, and reveals that mesophyll conductance decreases as leaves age in both C4 and C3 plants

Abstract: SummaryMesophyll conductance significantly, and variably, limits photosynthesis but we currently have no reliable method of measurement for C 4 plants.An online oxygen isotope technique was developed to allow quantification of mesophyll conductance in C 4 plants and to provide an alternative estimate in C 3 plants. The technique is compared to an established carbon isotope method in three C 3 species.Mesophyll conductance of C 4 species was similar to that in the C 3 species measured, and declined in both C 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
201
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(218 citation statements)
references
References 62 publications
(159 reference statements)
15
201
1
Order By: Relevance
“…One commonly used assumption is that g m of C 4 plants is infinite, and thus C i = C m . However, a recent study indicated that g m of C 4 plants is finite, although close to the high-end values of g m of C 3 plants (Barbour et al , 2016). In our study, assuming a lower range of g m across C i levels (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…One commonly used assumption is that g m of C 4 plants is infinite, and thus C i = C m . However, a recent study indicated that g m of C 4 plants is finite, although close to the high-end values of g m of C 3 plants (Barbour et al , 2016). In our study, assuming a lower range of g m across C i levels (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 53%
“…C i = C m . However, a recent study using a new oxygen isotope approach found that g m of C 4 species ranged between 0.66 and 1.8 mol m −2 s −1 measured at a leaf temperature of about 32 °C (Barbour et al , 2016). We calculated the minimum g m as: g mmin = A / C i (von Caemmerer et al , 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, an increase in g m with measurement temperature was reported by von Caemmerer and Evans (2015) and supported by data from Xiong et al (2015) in rice. A recent reported showed a decline in g m as leaves aged from fully expanded to senescing (Barbour et al, 2016), supporting that the above discrepancies reflect the importance of the experimental conditions and leaf age.…”
Section: Discussionmentioning
confidence: 72%
“…Oxygen isotopic signatures of transpired water (δ E ) were determined by mass balance (Dubbert et al, 2014a; Barbour et al, 2016): leftδE=uoutwoutδout-uinwinδinuoutwout-uinwin=woutδout-winδinwout-win-winwout(δout-δin)wout-win where u is flow rate [mol (air) s −1 ], w is mole fraction [mol (H 2 O) mol (air) −1 ] and δ is isotope ratio of air, where subscripts denote the incoming ( in ) and outgoing ( out ) air stream of the chamber. δ, w and u were measured by alternately connecting the L2120-i with the sample and reference gas flow of the GFS-3000.…”
Section: Methodsmentioning
confidence: 99%